Experiences with SARS-CoV-2 (Covid-19) in Trinidad and Tobago, a small island developing state: realities and opportunities - Darren Dookeeram; Seetharaman Hariharan; Ian Hambleton; Kareema Ali; Surujpaul Teelucksingh; Samuel Ramsewak; Dave Dookeeram; Sandeep Bhupendra Maharaj (Elsevier, 2023)
Summary: The COVID-19 pandemic has exerted significant global challenges that are expressed in a variety of socio-politico-economic scenarios, depending upon individual countries' preparedness and resilience. The impact COVID-19 in Small Island Developing States (SIDS), most of which are categorized as Lower and Middle-Income Countries, has been pronounced. Furthermore, many of these SIDS possess specific vulnerabilities to global threats. This paper contextualizes the experience of Trinidad and Tobago from some perspectives of geoeconomics, healthcare, and international relations. In many ways, the experience is similar to that of other SIDS with the inherent nuances of a post-colonial world. Trinidad and Tobago was ranked number one by the Oxford University COVID-19 Government Response Tracker (OxCGRT) "Lockdown rollback checklist: Do countries meet WHO recommendations for rolling back lockdown?". Despite the significant political support to combat the disease, by the end of 2022, the country had recorded over four thousand deaths and just over 50% of the population is vaccinated. This paper seeks to discuss the successes and challenges faced by this twin island state.